Odpowiedzi

2010-01-08T20:54:44+01:00
A) (3-2x) - (x-4) - (2x+5)= (3x-4) - (5x +7)
3-2x-x+4-2x-5=3x-4-5x-7
3+4-5+4+7=3x-5x+2x+x+2x
13=3x
x=13/3
x=4⅓

b) (4- x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
4-3-4-3+7=-2x-x+x+2x-x
1=-x
x=-1

c) (4x-5)+(x-7)-(2x-8) =(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
-5-7+8-4-6=-3x-x-4x-x+2x
-14=-7x
x=2


d) -(4-2x)-(2x+-4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x+4=3x-1+2x-5-7+3x
-4+4+1+5+7=3x+2x+3x-2x+2x
13=8x
x=13/8
x=1⅝

3 1 3
Najlepsza Odpowiedź!
2010-01-08T21:31:06+01:00
A) (3-2x) - (x-4) - (2x+5)= (3x-4) - (5x +7)
3-2x-x+4-2x-5 = 3x-4-5x-7
-3x=-13
x=13/3=4 i 1/3

b) (4- x)-(2x+3)+(x-4) = -(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
x=-1

c) (4x-5)+(x-7)-(2x-8) =(-3x+4)-(x-6)
4x-5+x-7-2x+8 = -3x+4-x+6
7x=14
x=2

d) -(4-2x)-(2x+-4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x+4 = 3x-1+2x-5-7+3x
8x=13
x=13/8 = 1 i 5/8